2009 Information and communications for development : (World Bank, 2009)
"Information and communications for development 2009 : extending reach and increasing impact" first examines the economic impact of mobile, broadband connectivity, and e-government applications. It highlights country experiences with different institutional arrangements for e-government and discusses policy options for advancing access to ICT infrastruture and services. It also reviews policy options that recourage the development of information technology (IT) and IT-enable services industries in the developing world.